Living out of the suitcase : is domestic tourism an effective tool for regional convergence : divergence of expenditure patterns in South Africa from 2013 to 2015? - Grobler, Adriaan Chris (Stellenbosch : Stellenbosch University, 2018)
Thesis (MPhil)--Stellenbosch University, 2018.